De novo genome assembly of rice bean (Vigna umbellata) – A nominated nutritionally rich future crop reveals novel insights into flowering potential, habit, and palatability centric – traits for efficient domestication - Kaul, Tanushri; Easwaran, Murugesh; Thangaraj, Arulprakash; Meyyazhagan, Arun; Nehra, Mamta; Raman, Nitya Meenakshi; Verma, Rachana; Sony, Sonia Khan; Abdel, Khaled Fathy; Bharti, Jyotsna; Gayacharan,; Badapanda, Chandan; et al. (Frontiers in Plant Science, 2022)
Rice bean is a less known and underutilized legume crop that has proved to be highly favourable due to its rich nutritional value in comparison with other members of the Vigna family. As an initiative to compose rice bean (Vigna umbellata) genomic resource, the size of 414 mega-base pairs with an estimate of 31276 highly confidential genes from 15521 scaffolds and functional coverage of 96.08% was sequenced from 30X coverage data from Illumina and PacBio platform. Rice bean genome assembly was found to be exquisitely close to V. angularis (experimental control/outgroup), V. radiata and V. unguiculata, however, V. angularis being the closest. Heuristically, the assembled genome was further aligned with 31 leguminous plants (13 complete genomes and 18 partial genomes), by collinearity block mapping. Further, we predicted similar discriminant results by complete CDS alignment. In contrast, 17 medically influential genomes from NIGMS-NIH, when compared with rice bean assembly for LCB clusters led to identification of more than 18000 genes from the entire selected medicinal genomes. Empirical construction of all genome comparisons revealed symplesiomorphic character in turn uncovering the lineage of genetic and functional features of rice beans. Significantly, we found deserving late-flowering genes, palatably-indexed uncommon genes that regulate various metabolite pathways, related to abiotic and biotic stress pathways and those that are specific to photoperiod and disease resistance and so on. Therefore, the findings from this report addresses the genomic value of rice bean to be escalated via breeding by allied and applied approaches.